Analiza instytucji świadka koronnego w Polsce - Zarzycka, Daria (Kortowski Przegląd Prawniczy, 2021)
The article presents the institution of the crown witness in Poland, as well as a process of obtaining this status. In addition, the conditions for the protection of both the crown witness and his relatives are indicated. An important element of the text is also the mention that this institu-tion has many supporters and opponents. The aim of the article was to analyze the institution of a crown witness, pointing its good and bad sides, as well as to look closer at the process of obtaining the that status. The conclusions that can be drawn are that crown witnesses can contribute to the resolution of even the most difficult cases regarding organized crime groups, while currently their testimony is not thoroughly verified. That may lead to wrongful convictions, so this institution should be refined by the legislator in such a way that the crown witness does not raise the slightest doubt as to his credibility.